A modified protocol of the alloxan technique for the induction of diabetes mellitus in Wistar rats - Abboud, Renato de Souza; Chagas, Mauricio Alves; Ribeiro, Ilma Cely de Amorim; Corrêa, Lanna Beatriz Neves Silva; Lange, Raquel Milhomem (Medicina Veterinária, 2020)
The chemical induction of diabetes mellitus in Wistar rats using alloxan is a commonly adopted scientific method for obtaining experimental models. Although a wide variety of induction protocols have been reported, no standard protocol has been defined due to high mortality rates, reversal, and failure of induction. Therefore, this study proposes an adaptation of the technique to induct diabetes mellitus through a 30-hour fast and a 150 mg/kg dosage of alloxan. The proposed technique has proved to be highly effective.